Potential and Limitations of Horizontal Management - Léger, Rémi (Minorités linguistiques et société / Linguistic Minorities and Society, 2012)
On 11 June 2010, ten leading scholars came together at the invitation of the Canadian Institute for Research on Linguistic Minorities to discuss the autonomy and recognition of Canada’s official language minority communities. In this article, I examine the implications of this workshop for Francophone minority community institutions by emphasizing and contextualizing main ideas and expanding on key proposals. First, I map out and explain how the implementation of horizontal management has increasingly curtailed community autonomy. Next, I catalog and discuss participants’ proposals for fostering greater autonomy for Francophone minority communities. Last, I sketch the potential and limitations of horizontal management.